2013
DOI: 10.1002/eji.201243152
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic effector pathways and IFN‐γ help protect against Japanese encephalitis

Abstract: Japanese encephalitis, caused by infection with the neurotropic flavivirus, Japanese encephalitis virus (JEV), is among the most important viral encephalitides in Asia. While previous studies established an essential role of Ab and type I IFN, it is still unclear if the cell-mediated immune responses, through their direct antiviral effector functions, contribute to protection against the fatal disease. We report here that mice defective in both the granule exocytosis and death receptor pathways of cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 54 publications
3
59
1
Order By: Relevance
“…Further investigations are needed to provide a more detailed mechanism to explain this high susceptibility to JEV. A recently published study by the authors showing the importance of IFN-γ production for protection against JE [10] may provide an answer. The advantages of this model, as well as the relatively fast reduction in antibody levels, warrant its utility for evaluating the protective efficacy of JE vaccine candidates, in particular, the induction of memory B cells that have protective functions without pre-existing neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…Further investigations are needed to provide a more detailed mechanism to explain this high susceptibility to JEV. A recently published study by the authors showing the importance of IFN-γ production for protection against JE [10] may provide an answer. The advantages of this model, as well as the relatively fast reduction in antibody levels, warrant its utility for evaluating the protective efficacy of JE vaccine candidates, in particular, the induction of memory B cells that have protective functions without pre-existing neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the signalling CXCL10/CXCR3 is implicated in the infiltration of virus-specific CD8 + T lymphocytes into the brain leading to a prolong survival of WNV-infected mice [33]. In JEV-infected mice, CD8 + T lymphocytes accumulate in the brain [27] and the activity of cytotoxic lymphocytes partly mediates protection against JEV [34]. Indeed, impaired activity and trafficking of CD8 + T-cell into the CNS contribute to increased mortality of CCR5-deficient mice exposed to JEV [27].…”
Section: Discussionmentioning
confidence: 99%
“…MHC class II is involved in the reactivation of virus-specific CD4 + T-lymphocytes. Helper T-cells accumulate in the CNS of JEV-infected mice [27] and are a critical source of IFN-γ which promotes JEV clearance [34]. In this context, it was interesting to note that human microglia exposed to live JEV showed weak modification of MHC class II on CX 3 CR1 + microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, WNV may evade NK-cell mediated killing by upregulation of MHC class I on infected cells. Lastly, although the depletion approach has been commonly used to determine the functional role of NK cells during in vivo flavivirus infection [31,42], it has been reported that NK cells can’t be fully depleted in all WNV- infected tissues [36]. …”
Section: Nk Cellsmentioning
confidence: 99%